Flexible diverticulotomy for Zenker's diverticulum – a bicentric study - Epping, Hendrik; Ziachehabi, Alexander; Spaun, Georg; Wewalka, Friedrich; Maieron, Andreas; Schöfl, Rainer (Zeitschrift für Gastroenterologie, 2022)
Introduction Flexible diverticulotomy is an established procedure for the treatment of Zenker's diverticulum. In a bicentric study, we investigated the development of the procedure since its introduction at the Ordensklinikum Linz Barmherzige Schwestern and Elisabethinen in 2010.Methods All flexible diverticulotomies performed between January 2010 and December 2019 at the above-mentioned clinics were evaluated retrospectively. Patients were divided into two 5-year periods (2010–2014 and 2015–2019) and statistical tests were performed for comparison of data.Results In all, 69 flexible diverticulotomies were performed. The procedure was technically successful in 93.5% of cases. No lethal outcome was encountered. Only 2 (2.9%) interventions led to serious complications which had to be treated in the intensive care unit. Mild complications occurred in 14.5% of cases. 54 patients were evaluated in the follow-up period; 11 (20.3%) patients experienced relapses of dysphagia. The primary intervention resulted in a significant improvement over the observation period. Patients in the second intervention group had shorter average hospital stays and longer recurrence-free intervals.Conclusion Flexible diverticulotomy is a safe and effective procedure for the treatment of Zenker's diverticulum. However, as the success rate appears to depend on the expertise and experience of the department, flexible diverticulotomy should be performed at centers with high caseloads.
Keywords: Ösophagus; flexible Divertikulotomie; Zenker-Divertikel